Hypothalamic‐pituitary‐adrenal (HPA) axis activity in adults with intellectual disabilities: a preliminary investigation. (25th April 2012) - Presland, A. D.; Clare, I. C. H.; Broughton, S.; Luke, L.; Wheeler, E.; Fairchild, G.; Watson, P. C.; Chan, W. Y. S.; Kearns, A.; Ring, H. A.
Abstract: Background Cortisol is a marker of physiological arousal, exhibiting a characteristic pattern of diurnal activity. The daily cortisol profile has been examined extensively and is atypical in a number of clinical disorders. However, there are very few studies focussing on the cortisol profile in adults with intellectual disabilities (ID). This paper reports a preliminary investigation into the nature of the cortisol profile in adults with mild or moderate ID and provides reflections on the challenges of psychophysiological research in this population. Methods On two consecutive days, 39 adults with mild or moderate ID each donated saliva samples for cortisol analysis, at multiple times between waking and evening. A comparison between these data and the published literature permitted a descriptive assessment of the cortisol awakening response (CAR) and diurnal profile. A variety of psychometric measures and an assessment of behavioural history were also collected in order to describe aspects of the participants' emotional and behavioural states. Results Individuals with ID exhibit a diurnal cortisol secretion profile, qualitatively similar to that of the typical, healthy, adult population. However, the findings also suggested a blunted CAR, warranting further investigation. There was also some evidence that cortisol secretion was affected by anxiety and a recent history of aggression. Conclusion While further work is required to characterise the CAR fully, there was no indication that the diurnal cortisol profile among people with ID differs from that of the typical population. This study also demonstrates that, although challenging, it is feasible, and acceptable to participants, to collect repeated physiological measures from men and women with mild and moderate ID.